Sexual harassment as experienced by nurses from selected healthcare facilities in Ghana - Aliu Mohammed; Edward Wilson Ansah; Daniel Apaak (BMC, 2023)
Abstract Background Workplace Sexual Harassment (WSH) remains a major occupational health hazard to many nurses globally. Despite the negative impact of WSH on health and safety of nurses, there are limited studies exploring sexual harassment experiences of nurses in the line of duty in Low- and middle-income countries (LMICs) including Ghana. Aim This study aimed at exploring the lived sexual harassment experiences among nurses working in healthcare facilities in the Central Region of Ghana. Method This study used a qualitative interpretive phenomenological approach (IPA). Data from 24 participants, 13 participants' written descriptive narratives of sexual harassment experiences (via online) and 11 telephone interviews were analysed concurrently using the IPA. Results Participants experienced verbal, non-verbal and physical forms of sexual harassment, often perpetrated by physicians, colleague workers, and patients. Most victims reacted passively to the acts sexual harassment and cases are often not reported despite the negative impact on victims' health. While some participants dealt with sexual harassment by accepting the behaviour as an inevitable part of their job, others either quit or intend to quit the job to avoid the harassers. Most participants are unaware of any workplace measure such as policy that addresses sexual harassment in the health sector in Ghana. Conclusion This study highlights the problems of sexual harassment against nurses in the healthcare sector in Ghana, and calls for urgent development of measures such as a sexual harassment policy to prevent occurrence and promote effective resolution of sexual harassment within the healthcare sector in the country. Sexual harassment against nurses could be hampering quality healthcare delivery in the region.